2011
DOI: 10.4322/acr.2011.018
|View full text |Cite
|
Sign up to set email alerts
|

Primary aortoesophageal fistula: a rare cause of acute upper gastrointestinal bleeding

Abstract: Acute upper gastrointestinal bleeding is a potentially life-threatening emergency, especially in the elderly. This condition accounts for approximately 1% of all emergency room admissions. Among the causes of such bleeding is aortoesophageal fistula, a dreaded but apparently rare condition, first recognized in 1818. The great majority of cases are of primary aortoesophageal fistula, caused by atheromatous aortic aneurysms or, less frequently, by penetrating aortic ulcer. The clinical presentation of aortoesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The diagnosis of mycotic aortic aneurysms can be greatly challenging due to the common nonspecific symptoms including the presence of fever and general malaise. AEF may present with the classical clinical symptoms known as Chiari triad which is characterised by central chest pain, dysphagia, and sentinel haemorrhage followed by exsanguinating hematemesis [ 6 ]. The imaging modality of choice for detection of AEF is multislice CT angiography, with 3D reconstructions being demonstrated in this case.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of mycotic aortic aneurysms can be greatly challenging due to the common nonspecific symptoms including the presence of fever and general malaise. AEF may present with the classical clinical symptoms known as Chiari triad which is characterised by central chest pain, dysphagia, and sentinel haemorrhage followed by exsanguinating hematemesis [ 6 ]. The imaging modality of choice for detection of AEF is multislice CT angiography, with 3D reconstructions being demonstrated in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple parietal ulcers were observed on the descending aorta ( Figure 4 ), which resulted from the ulceration of a previous atherosclerotic plaque. PAUs penetrate the aortic wall from the internal elastic lamina to the arterial media; the hematoma is initially contained by the tunica adventitia, leading to a pseudoaneurysm formation ( 10 ). Therefore, we can see a hematoma of 40 × 60 mm in the CTA due to active contrast media extravasation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various reports of thoracic PAUs associated with a primary aortoesophageal fistula, our second case is remarkable as it is the first report of an abdominal PAU causing a PAEF in the English literature. [10][11][12][13] Vujcic et al recently reported a case of an aorto-appendicular fistula which may be related to an abdominal PAU; however, the authors suggested that undetected chronic appendicitis was the actual cause of the degradation of the aortic wall. 14 In our case, a focal penetrating ulcerative lesion of the infrarenal abdominal aorta evolved from an atherosclerotic plaque to a contained rupture inducing a PAEF.…”
Section: Discussionmentioning
confidence: 99%